Police bail with conditions. Perspectives on the use, misuse and consequences af a new police power - Raine, John W. (The British journal of criminology, 1997)
This paper reports findings from research on the use of a new power granted to the police to attach conditions to police bail. It explores a range of other issues concerning the new power and its use at three different levels. First is the constitutional level, where the implications are discussed of extending liberty-constraining powers from an independent judiciary into the executive arm of the state. Second is the policy and practice level, where consideration is given to the purposes and underlying principles that guide police decisions about the use or otherwise of the new power. Third is the operational level, where the study highlights important issues around the use of the power within the semi-private context of the police station custody suite. In addressing these issues, the paper also explores important questions about who gets police bail with conditions, why, and with what effects and consequences